Trimethyl chitosan postoperative irrigation solution modulates inflammatory cytokines related to adhesion formation. (15th July 2022) - Abueva, Celine DG.; Ryu, Hyun Seok; Park, So Young; Lee, Hayoung; Padalhin, Andrew R.; Min, Jun Won; Chung, Phil-Sang; Woo, Seung Hoon
Abstract: Lavage or irrigation has been instilled in surgical practice for wound clearance and surgical site infection prevention during and after surgery. Herein, we developed a new irrigation solution using trimethyl chitosan (TMC), a quaternized chitosan derivative. The TMC-saline irrigation solution developed in the study possesses highly effective bactericidal properties with hemostatic and anti-adhesion properties. The anti-adhesion property of TMC was investigated in relation to inflammatory cytokine response and wound healing. TMC-saline irrigation solution showed reduced pro-inflammatory cytokine protein and gene expressions relevant in the cascade of wound healing and cytokine-related orchestration of postoperative adhesion formation. Further development of this multifunctional TMC-saline irrigation solution can be beneficial for surgical applications and postoperative wound management. Graphical abstract: Unlabelled Image